Polska tożsamość i polski nacjonalizm. Etnologiczna interpretacja zjawiska - Schmidt, Paweł (Zeszyty Wiejskie, 2010)
The author, starting from the perception of disputes that take place in public debate on the vision of the Polish nation and state, deals with the problem of the sense of the Polish national identity in everyday life, steeped in experiences indirectly transmitted by media. The author treats the national identity as a category of analysis or political fiction, because he concentrates on the occurrence of nationality – one of the identification of constructing social identity of every man, felt and realized in the sphere of everyday life. Nationality and terms such as nation, society and the State are understood differently by both sides of disputes – right-wing conservatives and left-wing conformists. But in both cases sense of the nation and the society is influenced by nationalist ideology that strives for a homogeneous treatment of the nation and state. It makes a synonymic understanding of that terms which describes the nation and society. The author presents two varieties of nationalism: radical nationalism and banal nationalism, identifying the latter as “national mentality” shared by the general of Polish society. In his opinion attachment to the slogans professed by Polish nationalists and inquiring them into knowledge about the world also different understandings of terms nation and society by the sides of the dispute makes public debate about sense of Polish nation impossible.